Darth Paper strikes back : an Origami Yoda book - Angleberger, Tom. (Amulet Books, 2011)
Harvey, upset when his Darth Paper finger puppet brings humiliation, gets Dwight suspended, but Origami Yoda asks Tommy and Kellan, now in seventh grade, to make a new casefile to persuade the School Board to reinstate Dwight.